PENGARUH MEKANISME CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP RISK MANAGEMENT DISCLOSURE - Barbara Gunawan; Yulia Nurul Zakiyah (Jurusan Akuntansi Politeknik Negeri Bandung, 2017)
Abstract: This study aims to examine the influence of corporate governance mechanisms, company size, and leverage towards risk management disclosure (RMD). Population on this study are all of nonfinancial companies listed in Indonesia Stock Exchange for periods 2014-2015. Independent variable examined in this study consisted of institutional ownership, board of commissioner size, auditor reputation, company size and leverage. The dependent variable examined in this study consisted of risk management disclosure. The sampling technique used in this study is purposive sampling. During observation of years there are 236 companies qualified as samples, thus the total number of sample for two years observe periods (2014-2015) is 472 companies. The method of data analysis is used multiple regression analysis with software IBM Statistical Package for Social Science (SPSS) Statistic Version 23.0. The result of this study showed that there are positive and significance effects between auditor reputation and company size towards risk management disclosure with each level of significance are 0,003 and 0,000. Institutional ownership, board of commissioner size and leverage have no significantly effects towards risk management disclosure.Keywords: Risk Management Disclosure, Corporate Governance Mechanisms, Institutional Ownership, Board of Commissioner Size, Auditor Reputation, and Leverage.